Sustainable Protein Recovery and Wastewater Valorization in Shrimp Processing by Ultrafiltration - Samar Ltaief; Aurélie Matéos; Adrien Forestier; Khaled Walha; Loubna Firdaous (Foods)
This study investigated the use of ultrafiltration for sustainable protein recovery and the treatment of shrimp washing wastewater (SWW). Three ultrafiltration membranes with molecular weight cut-offs of 5, 10, and 50 kDa were tested using a combined ultrafiltration–diafiltration process (UF-DF). The performance of each membrane was assessed based on protein recovery efficiency, chemical oxygen demand (COD) reduction, turbidity, fouling behavior, and cleaning efficiency. The 5 kDa membrane showed superior performance, achieving over 90% protein and COD rejection and producing the highest protein-enriched retentate. It also exhibited the lowest fouling index and best cleaning recovery, confirming its suitability for protein concentration and wastewater treatment. This research highlights UF-DF as a promising, eco-efficient technology for valorizing seafood processing effluents by recovering high-value proteins and reducing environmental discharge loads.